MODEL PELATIHAN GURU IPS, IPA TEMATIK TERPADU KURIKULUM 2013 DI SEKOLAH DASAR MUHAMMADIYAH KARTASURA - Tjipto Subadi; Budi Murtiyasa; Sutama Sutama; Anam Sutopo; Muhroji Muhroji (Universitas Muhammadiyah Surakarta, 2016)
The Aim of community service are; 1)Training of primary school teachers of Social Sciences, Natural Sciences based integrated thematic curriculum in 2013 with a scientific approach, 2) To improve the professional skills of primary school teachers of Social Sciences, Natural Sciences based integrated thematic curriculum in 2013 with a scientific approach, 3) To produce the guidance system of the teachers of Social Sciences, Natural Sciences based integrated thematic curriculum, 2013 in Muhammadiyah schools Kartasura. This is the approach of community service workshops, training and mentoring learning of Social Sciences, Natural Sciences based integrated thematic curriculum, 2013. The participants of Master of Social Sciences, Natural Sciences in SD Muhammadiyah Kartasura, His place in the School of Muhammadiyah Kartasura. The result of this devotion implementation; 1) Training of primary school teachers of Social Sciences, Natural Sciences based integrated thematic curriculum in 2013 with a scientific approach, using techniques to observe, to question, to reason, to try and form a network, and implemented with the collaboration system, using the three steps of the learning; introductory, core and cover. 2) To improve the professional skills of primary school teachers of Social Sciences, Natural Sciences based integrated thematic curriculum in 2013 with a scientific approach, using cooperative learning model learning with instructionalstrategies PBL (Problem Based Learning), DCL (descovery Learning), Jigsaw. Third this learning strategy, capable of creating a class to become a haven for students, namely; happy atmosphere for learners in the following study. This learning strategies,can improve learning achievement, namely; No increase in the value pretest to posttestvalues, namely: pretest values 60 = 50%: postes values 69 = 100%. 3) The resultingmodel of training primary school teachers of Social Sciences, Natural Sciences basedintegrated thematic curriculum in 2013 is a model mentoring based learning lesson study, with three stages (plan-do-see).